L2 rhythm production and musical rhythm perception in advanced learners of English - Jekiel, Mateusz (De Gruyter Mouton, 2022)
The aim of this research is to investigate the relation between musical aptitude and the acquisition of L2 rhythm by Polish advanced learners of English. A longitudinal study was conducted among 50 Polish students of English reading the “Please Call Stella” passage before and after an intensive two-semester accent training course supplemented by an extensive practical course in English phonetics and phonology. Participants also completed two musical hearing tests (Mandell 2009) and a survey on musical experience. Automated alignment was performed in DARLA (Reddy and Stanford 2015) and reviewed in Praat (Boersma and Weenink 2019). We compared the rhythm metrics calculated in Correlatore (Mairano and Romano 2010) before and after training and juxtaposed them against the pronunciation teachers’ results. We reported a significant difference between the scores for vocalic intervals across all rhythm metrics, indicating that participants’ produced higher vocalic variation after training, more similar to their teachers. However, we observed no significant relationship between the participants’ rhythm metric scores and their musical hearing test scores or musical experience, suggesting that musical aptitude might not play a crucial role in the L2 rhythm production in a formal academic learning environment.
Keywords: L2 rhythm; rhythm metrics; accent training; language and music; musical aptitude